Try Yuliarsih (10090154 / 2010) Influence Brand is Image and Price to Product Re-buying decision Mie Instan Indomies Brand By Studis Program College Student STKIP PGRIS Economy Western Sumatra - Yuliarsih, Try - (Pendidikan Ekonomi, 2014)
This research intent for menganalisis: 1 ) Influences brand is image to product rebuyingdecision Indomie by Studis Program College Student STKIP PGRIS EconomyWestern Sumatra, 2 ) price Influence to product re-buying decisions Indomie by StudisProgram College Student STKIP PGRIS Economies Western Sumatras, 3 ) Influences brandis image and price to product re-buying decision Indomie by Studis Program CollegeStudent STKIP PGRIS Economy Western SumatraThis observational time is done on august until September 2014. Observational typethat is utilized in this research is observational descriptive asosiatif. This observationalpopulation is all college student program studi angakatans Economy 2009 until 2013 totalone 1.098 person. Samples taking tech with Purposive is Sampling with sample amount asmuch 92 person. analisiss tech data: descriptive analisis and inductive analisis, which is quizmaximun likelihood, normality quiz, heteroskedastisitass quiz, multikoleniaritass quiz,autokorelasis quiz and analisis is bifilar regression with help programs SPSS version 16.0.Result observationaling to point out that: 1 ) available influence which positives andsignifikan among brand is image to product re-buying decision Indomie by studis programcollege student STKIP PGRIS Economy Western Sumatra bases to usufruct analisis data wasgotten to assess t computing > t table (5,245> 1,66), available positive influence and signifikan isprice to product re-buying decision Indomie by studis program college student STKIPPGRIS Economy Western Sumatra bases to usufruct analisis data was gotten to assess tcomputing > t table (7,007> 1,66), available positive influence and signifikan collectively amongbrand is image and price to product re-buying decision Indomie by studis program collegestudent STKIP PGRIS Economy Western Sumatra bases to usufruct analisis data f computing >Ftable (133,442> 3,10) and r Square 0,750.